Pengaruh Penerapan Blended Learning Terhadap Peningkatan Minat Belajar Peserta Didik Pada Mata Pelajaran IPS - Hesty Gellari Nastiti (Pendidikan IPS FKIP ULM, 2023)
Indonesia has experienced two years of the Covid-19 pandemic, which has significantly impacted the educational system. As the country now transitions into an endemic phase, there is a shift from predominantly distance learning to a limited face-to-face format. This transition presents challenges for social studies teachers in delivering their curriculum, leading to the need for the implementation of blended learning. This study aims to assess the effectiveness of blended learning in increasing the interest of class VIII students at SMPN 3 Bandung in social studies. The research design utilizes a quasi-experimental method with a nonequivalent pretest-posttest control group design. The research sample comprises 64 students from two classes: class VIII-3 as the experimental group and class VIII-1 as the control group. Data collection involved online questionnaires on learning interests via Google Forms and documentation. Subsequently, the collected data was analyzed using hypothesis testing in the SPSS version 20 application. The results of this study indicate that the use of blended learning in social studies had a significant impact on students' learning interests, with a significance value of 0.00, which is less than 0.05. Similarly, the control group, which employed conventional learning, also demonstrated a significant improvement in students' learning interest, with a significance value of 0.00. However, when comparing the learning interest between the experimental and control groups, there was no significant difference, as indicated by a significance value of 0.557, which is greater than 0.05.